Diagnostic accuracy of salivary biomarkers of bone turnover in identifying patients with periodontitis in a Saudi Arabian population - Joseph Betsy; Javali Mukhatar Ahmed; Abdul Khader Mohasin; Amanullah Mohammed; AlQahtani Nabeeh A. (Elsevier, 2019)
Background/purpose: Salivary markers of bone turnover are useful biomarkers for screening patients advanced periodontal diseases with alveolar bone loss. Hence, the purpose of this study was to determine the diagnostic accuracy of deoxypyridinoline-containing degradation fragment of the C-terminal telopeptide region of type I collagen (CTX), Osteocalcin (OC) and Osteonectin (ON) in identifying patients with alveolar bone loss (BL) due to periodontitis. Materials and method: Salivary levels of CTX, OC and ON were evaluated in ninety patients (group I, II and III with healthy, periodontitis without Type2 diabetes mellitus-T2DM and periodontitis with T2DM respectively). Group III was included since T2DM is very common among patients attending our clinics. Bleeding on probing (BOP), probing pocket depth (PPD) and BL were recorded for these patients. Results: The concentrations of salivary CTX, OC, and ON were higher in subjects with periodontitis than in controls. Significant correlations were found between these biomarkers and periodontal parameters. CTX, OC, and ON could discriminate between healthy (group I) and diseased (group II & III) regarding BL with excellent sensitivity (90.2-100%) and good specificity (62.1-96.6%). ROC curve gave excellent discrimination regarding BL (AUC: 0.926-0.958) and PPD (AUC: 0.904-0.915). However, none of the cut-off values gave good discrimination regarding BOP. Conclusion: It can be concluded that CTX, OC, and ON correlated well with BL and PPD. Among the three biomarkers, ON at 81.80 ng/ml gave the best discrimination for presence or absence of bone loss. Keywords: Salivary, C-terminal telopeptide region of type I collagen (CTX), Osteocalcin (OC), Osteonectin (ON), Alveolar bone loss (BL), Probing pocket depth (PPD)